Plasmon enhancement of thiacyanine J-aggregates luminescence in polymer films - Sorokin, A.V.; Pereverzev, N.V.; Liakh, V.M.; Borovoy, I.A.; Yefimova, S.L. (Functional Materials, 2015)
Formation of thiacyanine dye J-aggregates in layered polymer films has been studied. This process leads to the J-aggregates spectral bands widening as a result of static disorder increasing. To enhance the J-aggregate luminescence the effect of their interaction with plasmon resonances of silver nanoparticles has been used. It was found that about 4-fold luminescence enhancement for thiacyanine J-aggregates in the polymer films could be obtained at 15 nm distance from silver nanoparticles.